Correlates of Pisciculture Technology Adoption in Jagatsinghpur District of Odisha - Malla, Aditya Kumar; Behera, Jeebanjyoti (Indian Journal of Extension Education, 2020)
According to the Food and Agriculture Organization (FAO), fish output in India doubled between 1990 andÂ 2010. Fisheries sector is a source of livelihood for people engaged in fully, partially or in subsidiary activities. Its an integral component of rural development programme and its requirement of capital investment is relativelyÂ low and short gestation period. Per hectare annual income from pisciculture is much higher than that of crop production and pisciculture may appear to be a viable proposition for small and marginal farmers. The youth entrepreneur can generate more income from a small area of land by pisciculture in comparison to other crops. Odisha ranks 10th in terms of production of fish and it produces almost 4.50 percent of the total fish production of the country. The present study conducted in Ersama, Naugaon and Tirtol blocks of Jagatsinghpur district on 110 (hundred ten) number of respondents. More than three-fourth of the respondents (73.63%) had medium level of adoption, whereas only 15.45 per cent of the respondents had high adoption. Pisciculture technology adoption was found negative and non-significant with their age and innovation proneness and found positive and significant with their education, mass media exposure, socio-economic status, annual income and risk orientation.